An Improved Strategy to Recover Large Fragments of Functional Human Neutrophil Extracellular Traps - Barrientos, Lorena; Marin-Esteban, Viviana; de Chaisemartin, Luc; Lievin le moal, Vanessa; Sandre, Catherine; Bianchini, Elsa; Nicolas, Valerie; Pallardy, Marc; Chollet-Martin, Sylvie (Frontiers in Immunology, 2013)
Netosis is a recently described neutrophil function that leads to the release of neutrophil extracellular traps (NETs) in response to various stimuli. NETs are filaments of decondensed chromatin associated with granular proteins. In addition to their role against microorganisms, NETs have been implicated in autoimmunity, thrombosis and tissue injury. Access to a standardized source of isolated NETs is needed to better analyze the roles of NETs. The aim of this study was to develop a procedure yielding soluble, well-characterized NET preparations from fresh human neutrophils. The calcium ionophore A23187 was chosen to induce netosis, and the restriction enzyme Alu I was used to prepare large NET fragments. DNA and proteins were detected by electrophoresis and specific labeling. Some NET proteins (histone 3, lactoferrin) were quantified by western blotting, and dsDNA was quantified by immunofluorescence. Co-existence of dsDNA and neutrophil proteins confirmed the quality of the NET preparations. Their biological activity was checked by measuring elastase activity and bacterial killing against various strains. Interindividual differences in histone 3, lactoferrin, elastase and dsDNA relative contents were observed in isolated NETs. However, the reproducibility of NET preparation and characterization was validated, suggesting that this interindividual variability was rather related to donor variation than to technical bias. This standardized protocol is suitable for producing, isolating and quantifying functional NETs that could serve as a tool for studying NET effects on immune cells and tissues.